Self-growing protocell models in aqueous two-phase system induced by internal DNA replication reaction - Yoshihiro Minagawa; Moe Yabuta; Masayuki Su’etsugu; Hiroyuki Noji (Nature Communications, 2025)
Abstract The bottom-up reconstitution of self-growing artificial cells is a critical milestone toward realizing autonomy and evolvability. However, building artificial cells that exhibit self-growth coupled with internal replication of gene-encoding DNA has not been achieved yet. Here, we report self-growing artificial cell models based on dextran-rich droplets in an aqueous two-phase system of poly(ethylene glycol) (PEG) and dextran (DEX). Motivated by the finding that DNA induces the generation of DEX-rich droplets, we integrate DNA amplification system with DEX-rich droplets, which exhibited active self-growth. We implement the protocells with cell-free transcription-translation systems coupled with DNA amplification/replication, which also show active self-growth. Considering the simplicities in terms of the chemical composition and the mechanism, these results underscore the potential of DEX droplets as a foundational platform for engineering protocells, giving implications for the emergence of protocells under prebiotic conditions.